Factors Affecting Land Degradation in the Arid Regions of Afghanistan and Mitigation Approaches - Ahamadzai, Mohammad Amin; Rahil , Amrullah; Mangal, Mohammad Qayoom (Journal of Natural Sciences – Kabul University, 2026)
As in the rest of the world, desertification is a serious threat in Afghanistan, driven by overgrazing, climate change, and soil degradation. This research aims to identify the main factors of land degradation and to determine strategies to combat this disaster. The importance and necessity of research is to prevent land degradation and to achieve higher agricultural production. More than 300 articles have been studied to write the paper. The articles utilized were those in which the research context was very similar to that of Afghanistan. The findings revealed that reforestation is an essential measure in combating land desertification. Additionally, promoting sustainable grazing, collecting rainwater, and using modern irrigation systems are crucial steps for addressing land degradation in Afghanistan. These approaches not only reduce the impacts of desertification but also contribute to environmental development.